Transcription Factor Repurposing Offers Insights into Evolution of Biosynthetic Gene Cluster Regulation - Wenjie Wang (American Society for Microbiology, 2021)
ABSTRACT The fungal kingdom has provided advances in our ability to identify biosynthetic gene clusters (BGCs) and to examine how gene composition of BGCs evolves across species and genera. However, little is known about the evolution of specific BGC regulators that mediate how BGCs produce secondary metabolites (SMs). A bioinformatics search for conservation of the Aspergillus fumigatus xanthocillin BGC revealed an evolutionary trail of xan-like BGCs across Eurotiales species. Although the critical regulatory and enzymatic genes were conserved in Penicillium expansum, overexpression (OE) of the conserved xan BGC transcription factor (TF) gene, PexanC, failed to activate the putative xan BGC transcription or xanthocillin production in P. expansum, in contrast to the role of AfXanC in A. fumigatus. Surprisingly, OE::PexanC was instead found to promote citrinin synthesis in P. expansum via trans induction of the cit pathway-specific TF, ctnA, as determined by cit BGC expression and chemical profiling of ctnA deletion and OE::PexanC single and double mutants. OE::AfxanC results in significant increases of xan gene expression and metabolite synthesis in A. fumigatus but had no effect on either xanthocillin or citrinin production in P. expansum. Bioinformatics and promoter mutation analysis led to the identification of an AfXanC binding site, 5′-AGTCAGCA-3′, in promoter regions of the A. fumigatus xan BGC genes. This motif was not in the ctnA promoter, suggesting a different binding site of PeXanC. A compilation of a bioinformatics examination of XanC orthologs and the presence/absence of the 5′-AGTCAGCA-3′ binding motif in xan BGCs in multiple Aspergillus and Penicillium spp. supports an evolutionary divergence of XanC regulatory targets that we speculate reflects an exaptation event in the Eurotiales. IMPORTANCE Fungal secondary metabolites (SMs) are an important source of pharmaceuticals on one hand and toxins on the other. Efforts to identify the biosynthetic gene clusters (BGCs) that synthesize SMs have yielded significant insights into how variation in the genes that compose BGCs may impact subsequent metabolite production within and between species. However, the role of regulatory genes in BGC activation is less well understood. Our finding that the bZIP transcription factor XanC, located in the xanthocillin BGC of both Aspergillus fumigatus and Penicillium expansum, has functionally diverged to regulate different BGCs in these two species emphasizes that the diversification of BGC regulatory elements may sometimes occur through exaptation, which is the co-option of a gene that evolved for one function to a novel function. Furthermore, this work suggests that the loss/gain of transcription factor binding site targets may be an important mediator in the evolution of secondary-metabolism regulatory elements.